How to Improve the Performance of Public Elementary Schools? an Empirical Evidence from Indonesia - Kamaludin, Kamaludin (Jurnal Prima Edukasia, 2023)
This study aims to assess the construct validity of public elementary school performance from the proposed performance theory so that the observed variables can form a latent variable. This study used a quantitative approach with a measurement model in the form of First Order Confirmatory Factor Analysis. The sample in this study amounted to 233 principals of public elementary schools. Meanwhile, the location in this study is Brebes Regency, Central Java Province, Indonesia. Then, the data analysis in this research starts with developing the theoretical model, making a causality relationship path diagram, selecting the input matrix and obtaining the model estimate, assessing the identification of the structural model, and assessing the criteria of Goodness of Fit. This study reveals variables for measuring school performance, such as content standards, process standards, graduate competency standards, educator and education staff standards, facilities and infrastructure standards, management standards, financing standards, and education assessment standards, indicating that three observational variables are not significant and invalid in forming school performance latent variables, namely standards of educators and educational staff, standards of facilities and infrastructure, and standards of financing. In this regard, this research makes a practical contribution, namely that there is a need to change the orientation of fulfilling national education standards, which leads to school assessment based on performance appraisal based on curriculum development and implementation, teacher professional development, and optimizing the responsibility of stakeholders to improve educational quality so that schools able to provide optimal performance in providing services to the community.